2018
DOI: 10.1109/lcomm.2018.2848929
|View full text |Cite
|
Sign up to set email alerts
|

Robust Energy Harvesting FD Transmission: Interference Suppression Versus Exploitation

Abstract: We explore robust designs to jointly minimize the total uplink and downlink transmit power and maximize the total harvested energy in a full duplex system with imperfect channel state information. We first formulate an optimization, where multiuser interference (MUI) is suppressed. We then propose an optimization, where the MUI is rather exploited, both as useful energy and information power, for guaranteeing quality of service and energy harvesting constraints. To tackle the nonconvexity of the formulations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…CI exploitation can also be applied to FD communications for additional performance improvements, as recently studied in [101]- [103] for both PSK and QAM constellations. The CIbased PM problem in a multi-user FD system is considered in [101] and [102], where a multi-objective optimization via the weighted Chebycheff method is employed to study the tradeoff between the two desirable design objectives, which are the total downlink transmit power at the BS and the total uplink power from the UEs.…”
Section: Full-duplex (Fd) Communicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…CI exploitation can also be applied to FD communications for additional performance improvements, as recently studied in [101]- [103] for both PSK and QAM constellations. The CIbased PM problem in a multi-user FD system is considered in [101] and [102], where a multi-objective optimization via the weighted Chebycheff method is employed to study the tradeoff between the two desirable design objectives, which are the total downlink transmit power at the BS and the total uplink power from the UEs.…”
Section: Full-duplex (Fd) Communicationsmentioning
confidence: 99%
“…Importantly, the multi-objective framework allows the flexible tradeoff between the uplink power savings and the downlink power savings, which further leads to an improvement in the overall energy efficiency. In addition, CI-based FD communications have also been considered in the presence of imperfect CSI in [103], where a robust design for the joint minimization of the uplink and downlink transmit power and maximization of the harvested energy is studied subject to channel estimation errors. It is shown by numerical results that the gain in the harvested energy can be as large as 5dBm with an increase in the downlink transmit power.…”
Section: Full-duplex (Fd) Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, although the downlink MUI is exploited, the power gains extend to the uplink through the self-interference serving as the link [9]. Similarly, a robust multi-user FD design with simultaneous wireless information and power transfer (SWIPT) was investigated in [10].…”
Section: Introductionmentioning
confidence: 99%
“…In [? ], [4], [5], the authors used the knowledge of the DL signals at the FD BS to exploit multi-user interference (MUI) instead treating the MUI as unwanted as in traditional interference suppression techniques. In addition, it was shown that by exploiting the downlink MUI, the downlink transmit power is reduced significantly, although the downlink MUI is exploited, the power gains extend to the uplink through the self-interference serving as the link [4].…”
Section: Introductionmentioning
confidence: 99%